2016
DOI: 10.3945/jn.115.223420
|View full text |Cite
|
Sign up to set email alerts
|

Neither Preconceptional Weekly Multiple Micronutrient nor Iron–Folic Acid Supplements Affect Birth Size and Gestational Age Compared with a Folic Acid Supplement Alone in Rural Vietnamese Women: A Randomized Controlled Trial

Abstract: Weekly supplementation with MMs or IFA before conception did not affect birth outcomes compared with FA in rural Vietnamese women. The trial was registered at clinicaltrials.gov as NCT01665378.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 29 publications
1
60
1
Order By: Relevance
“…After testing positive for pregnancy, all of the women were given iron and folate daily until delivery. Preconception micronutrient supplementation did not alter fetal growth (22), but other outcomes are still under study.…”
Section: Periconception Nutrition Intervention Trials: Past and Ongoingmentioning
confidence: 92%
See 1 more Smart Citation
“…After testing positive for pregnancy, all of the women were given iron and folate daily until delivery. Preconception micronutrient supplementation did not alter fetal growth (22), but other outcomes are still under study.…”
Section: Periconception Nutrition Intervention Trials: Past and Ongoingmentioning
confidence: 92%
“…Reproduced from reference 41 with permission. symposium, 2 other interventions were discussed-a nutrientrich snack provided to Indian women (16), and a micronutrient supplement intervention (22). Nutrition education is another option.…”
Section: Next Stepsmentioning
confidence: 99%
“…Preconception underweight is associated with an increased risk of intrauterine growth retardation resulting in an SGA infant [20, 22]. Self-reported folic acid supplement during preconception, which aids fetal development, is associated with higher birthweight in children of underweight mothers [23, 24]. Adolescent pregnancies result in negative consequences for both the mother and infant.…”
Section: Linear Growth From Preconception To Beyond the First 1000 Dmentioning
confidence: 99%
“…We conducted a large double-blind randomized controlled trial of preconception micronutrient supplementation aiming to improve maternal health and birth outcomes (PRECONCEPT) [13, 14]. We have previously reported the findings from a qualitative study of beliefs and attitudes related to adherence to preconception and prenatal micronutrient supplementation that was conducted in a sub-sample of pre-pregnant, pregnant, and postpartum participants in the PRECONCEPT study [15], and found that women reported that they were more likely to adhere to supplements during pregnancy, as they considered them necessary for their and their offspring’s well-being.…”
Section: Introductionmentioning
confidence: 99%